Skip to content
Related Articles

Related Articles

Improve Article
Class 10 RD Sharma Solutions – Chapter 9 Arithmetic Progressions – Exercise 9.2
  • Last Updated : 08 Dec, 2020

Problem 1: Show that the sequence defined by an = 5n – 7 is an A.P., find its common difference.

Solution:

Given:

 an = 5n – 7

Now putting n = 1, 2, 3, 4,5 we get,

a1 = 5.1 – 7 = 5 – 7 = -2



a2 = 5.2 – 7 = 10 – 7 = 3

a3 = 5.3 – 7 = 15 – 7 = 8

a4 = 5.4 – 7 = 20 – 7 = 13

We can see that,

a2 – a1 = 3 – (-2) = 5

a3 – a2 = 8 – (3) = 5

a4 – a3 = 13 – (8) = 5

Since, the successive difference of list is same i.e 5

∴ The given sequence is in A.P and have common difference of 5

Problem 2: Show that the sequence defined by an = 3n2 – 5 is not an A.P.

Solution:

Given: 

an = 3n2 – 5

Now putting n = 1, 2, 3, 4 we get,

a1 = 3.1.1 – 5= 3 – 5 = -2

a2 = 3.2.2 – 5 = 12 – 5 = 7

a3 = 3.3.3 – 5 = 27 – 5 = 22

a4 = 3.4.4 – 5 = 48 – 5 = 43

We can see that,



a2 – a1 = 7 – (-2) = 9

a3 – a2 = 22 – 7 = 15

a4 – a5 = 43 – 22 = 21

Since, the successive difference of list is not the same 

∴ The given sequence is not in A.P 

Problem 3: The general term of a sequence is given by an = -4n + 15. Is the sequence an A.P.? If so, find its 15th term and the common difference.

Solution:

Given:

 an = -4n + 15

Now putting n = 1, 2, 3, 4 we get,

a1 = -4.(1) + 15 = -4 + 15 = 11

a2 = -4.(2) + 15 = -8 + 15 = 7

a3 = -4.(3) + 15 = -12 + 15 = 3

a4 = -4.(4) + 15 = -16 + 15 = -1

We can see that,

a2 – a1 = 7 – (11) = -4

a3 – a2 = 3 – 7 = -4

a4 – a3 = -1 – 3 = -4

Since, the successive difference of list is same i.e -4

∴ The given sequence is in A.P and have common difference of -4

Hence, the 15th term will be



a15 = -4(15) + 15 = -60 + 15 = -45

And, a15 = -45

Problem 4: Write the sequence with nth term :

(i) an = 3 + 4n

Solution:

Given:

an = 3 + 4n

Now putting n = 1, 2, 3, 4 we get,

a1 = 3 + 4.1 = 7 

a2 = 3 + 4.2 = 11

a3 = 3 + 4.3 = 15

a4 = 3 + 4.4 = 19

∴ The sequence is 7, 11, 15, 19

We can see that,

a2 – a1 = 11 – (7) = 4

a3 – a2 = 15 – (11) = 4

a4 – a3 = 19 – (15) = 4

Since, the successive difference of list is same i.e 4

∴ The given sequence is in A.P

(ii) an = 5 + 2n

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 5 + 2.1 = 7

a2 = 5 + 2.2 = 9

a3 = 5 + 2.3 = 11

a4 = 5 + 2.4 = 13

∴ The sequence is 7, 9, 11, 13

We can see that,

a2 – a1 = 9 – (7) = 2

a3 – a2 = 11 – (9) = 2

a4 – a3 = 13 – (11) = 2

Since, the successive difference of list is same i.e 2

∴ The given sequence is in A.P

(iii) an = 6 – n

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 6 – 1 = 5

a2 = 6 – 2 = 4

a3 = 6 – 3 = 3

a4 = 6 – 4 = 2

∴ The sequence is 5, 4, 3, 2

We can see that,

a2 – a1 = 4 – (5) = -1

a3 – a2 = 3 – (4) = -1

a4 – a3 = 2 – (3) = -1

Since, the successive difference of list is same i.e -1

∴ The given sequence is in A.P

(iv) an = 9 – 5n

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 9 – 5.1 = 4

a2 = 9 – 5.2 = -1

a3 = 9 – 5.3 = -6

a4 = 9 – 5.4 = -11

∴ The sequence is 4, -1, -6, -11

We can see that,

a2 – a1 = -1 – (4) = -5

a3 – a2 = -6 – (-1) = -5

a4 – a3 = -11 – (-6) = -5

Since, the successive difference of list is same i.e -5

∴ The given sequence is in A.P

Problem 5: The nth term of an A.P. is 6n + 2. Find the common difference.

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 6.1 + 2 = 8

a2 = 6.2 + 2 = 14

a3 = 6.3 + 2 = 20

a4 = 6.4 + 2 = 26

We can see that,

a2 – a1 = 14 – (8) = 6

a3 – a2 = 20 – (14) = 6

a4 – a3 = 26 – (20) = 6

Hence, the common difference is 6

Problem 6: Justify whether it is true to say that the sequence, having following nth term is an A.P.

(i) an = 2n – 1

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 2.1 – 1 = 1

a2 = 2.2 – 1 = 3

a3 = 2.3 – 1 = 5

a4 = 2.4  – 1 = 7

We can see that,

a2 – a1 = 3 – (1) = 2

a3 – a2 = 5 – (3) = 2

a4 – a3 = 7 – (5) = 2

Since, the successive difference of list is same i.e 2

Hence, the given sequence is in A.P

(ii) an = 3n² + 5

Solution:

Now putting n = 1, 2, 3, 4 we get,

a1 = 3.1.1 + 5 = 8

a2 = 3.2.2 + 5 = 17

a3 = 3.3.3 + 5 = 32

a4 = 3.4.4 + 5 = 53

We can see that,

a2 – a1 = 17 – (8) = 9

a3 – a2 = 32 – (17) = 15

a4 – a3 = 53 – (32) = 21

Since, the successive difference of list is not the same 

Hence, the given sequence is not in A.P

(iii) an = 1 + n + n²

Solution:

Now putting n = 1, 2, 3 we get,

a1 = 1 + 1 + 1.1 = 3

a2 = 1 + 2 + 2.2 = 7

a3 = 1 + 3 + 3.3 = 13

We can see that,

a2 – a1 = 7 – (3) = 4

a3 – a2 = 13 – (7) = 6

Since, the successive difference of list is not the same

Hence, the given sequence is not in A.P

My Personal Notes arrow_drop_up
Recommended Articles
Page :